Guidelines for surveying soil and land resources - McKenzie, Neil J. 1958- (CSIRO Pub., 2007)
Provides guidelines to promote the development and implementation of consistent methods and standards for conducting soil and land resource surveys in Australia.
Keywords: Soil surveys -- Australia -- Handbooks, manuals, etc.; Land use surveys -- Australia -- Handbooks, manuals, etc.; Landforms -- Australia -- Classification -- Handbooks, manuals, etc.; Australia.; elektronické knihy; electronic books